Determine and analyze the magnetic field magnitude over the Universiti Tun Hussein Onn Malaysia area using magnetometer - Noor Syazana Arshad
In this project, the magnitude of the magnetic field were observed and analyzed around Universiti Tun Hussein Onn (UTHM) using Magnetometer. The measurement of magnetic field magnitude was obtained from Overhauser Magnetometer reading. The magnetic field data was analyzed using Surfer 10 software. Initially, the Overhauser Magnetometer was assembled and the magnetic survey was conducted in walking mode. The magnetic field survey locations are Wireless and Radio Science Center (WARAS), Open Field, UTHM Library and Tun Fatimah College. The survey was conducted on 1st, 17th and 30th November 2011 also on 9th and 12th December 2011, on three periods on each survey day, which are morning, noon and evening. Consecutively, the results were given in the form of contour map of magnetic field on each survey location which was later compared with the International Geomagnetic Reference Field (IGRF-11). IGRF-11 is a standard mathematical description of the Earth's main magnetic field. The contour map reveals that the Earths magnetic field fluctuates unpredictably during geomagnetic storm occasion and yet fluctuates considerably during quiet geomagnetic days. The magnetic field survey data shows that the Earths magnetic field varies throughout the day thus proved that IGRF-11 geomagnetic model cannot be used to predict exact value of Earths magnetic field magnitude. It can be concluded that the space weather disturbance greatly affect the Earths magnetic field in equatorial region.